Flow Stagnation under Single and Two-Phase Natural Circulation Conditions in the APEX-CE Test Facility - José N. Reyes (Science and Technology of Nuclear Installations)
Natural circulation experiments were conducted at Oregon State University using the advanced plant experiment (APEX-CE) integral system test facility as configured to simulate a typical 2×4 Combustion Engineering nuclear steam supply system. This paper describes the mechanisms by which natural circulation flow was interrupted under single-phase and two-phase natural circulation conditions in APEX-CE.